PENGEMBANGAN MEDIA PEMBELAJARAN E-BOOKLET UNTUK MENINGKATKAN PEMAHAMAN KONSEP PADA MATERI PEMANASAN GLOBAL DI KELAS X SMA N 2 KOTA BENGKULU - Yunita, Cindi; Hamdani, Dedy; Putri, Desy H (Kumparan Fisika, 2025)
The purpose of this study is to (a) produce a suitable learning media in the form of e-booklet learning media to increase the understanding of concepts in global warming material for grade X students, and (b) to describe the improvement of students' understanding of concepts after being taught by using e-booklet learning media on global warming material in class X. The research method used is Research and Development (R and D) with the ADDIE model. The instruments used in this study are questionnaires, observations, interviews, and concept comprehension tests on global warming materials. The results obtained in the research that has been carried out at SMA Negeri 2 Bengkulu City in class X 4 for products that have been validated by experts obtained a score with a category that is very suitable for use. Based on the results of the N-gain calculation obtained through the Pretest and Posttest, the concept understanding indicator for the first indicator in the medium category, the second indicator in the high category, the third indicator in the medium category, the fourth indicator in the high category, the fifth indicator in the high category, the sixth indicator in the medium category. The increase in medium and high concept understanding shows that e-booklet learning media can improve students' understanding of concepts. Thus, it can be concluded that e-booklet learning media is suitable for use and can increase students' understanding of concepts. Keywords: E-booklet, Conceptual understanding, Global warming